2020
DOI: 10.1101/2020.07.14.202176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A general-purpose mechanism of visual feature association in visual word identification and beyond

Abstract: Writing systems are a recent cultural invention, which makes it unlikely that specific cognitive mechanisms have developed through selective pressure for reading itself. Instead, reading might capitalize on evolutionary older mechanisms that originally supported other tasks. Accordingly, animals such as baboons can be trained to perform visual word recognition. This suggests that the visual mechanisms supporting reading might be phylogenetically old and domain-general. Here we propose that if the human reading… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…These findings well complement non-arbitrary perspectives on language processing (Dingemanse et al, 2015). The semantic effect found for pseudowords can indeed be explained with reference to the humans' tendency to detect systematic and statistical regularities in the (language) environment (Romberg & Saffran, 2010;Vidal, Viviani, Zoccolan, & Crepaldi, 2021), here expressed in the form of nuanced distributional patterns of sub-word information. Accordingly, seminal studies have shown that children can extract syllabic patterns based on transitional probabilities between elements, when these patterns are presented in a continuous stream (Saffran, Aslin, & Newport, 1996).…”
Section: Discussionsupporting
confidence: 74%
“…These findings well complement non-arbitrary perspectives on language processing (Dingemanse et al, 2015). The semantic effect found for pseudowords can indeed be explained with reference to the humans' tendency to detect systematic and statistical regularities in the (language) environment (Romberg & Saffran, 2010;Vidal, Viviani, Zoccolan, & Crepaldi, 2021), here expressed in the form of nuanced distributional patterns of sub-word information. Accordingly, seminal studies have shown that children can extract syllabic patterns based on transitional probabilities between elements, when these patterns are presented in a continuous stream (Saffran, Aslin, & Newport, 1996).…”
Section: Discussionsupporting
confidence: 74%
“…Since a-priori, the presence of patterns within stimuli are unknown, the brain might automatically encode their TP in order to detect potential structure and violations of such. Artificial grammar learning studies, where subjects learn patterns of TP to which they were never exposed before, confirm the relevance of this TP encoding in language learning (15,31,32,36,53).…”
Section: The Brain Encodes Tps In Random Stimulus Sequencesmentioning
confidence: 63%
“…Object space is then proposed as a framework to simplify and abstract visual object representation by projecting critical features into a representational space with a finite number of orthogonal axes (2,4,5,27,28). The finite number of axes prevents the confusion of processing infinite visual details within a limited time, and statistical orthogonality among axes effectively reduces the redundancy of visual details (29,30). Moreover, the existence of object space also permits perceptual invariance (2,28) and generalization (5) during object recognition.…”
Section: Discussionmentioning
confidence: 99%